Bactericidal and Anti-biofilm Effects of Polyhexamethylene Biguanide in Models of Intracellular and Biofilm of Staphylococcus aureus Isolated from Bovine Mastitis - Kamaruzzaman, Nor F.; Chong, Stacy Q. Y.; Edmondson-Brown, Kamina M.; Ntow-Boahene, Winnie; Bardiau, Marjorie; Good, Liam (Frontiers in Microbiology, 2017)
Staphylococcus aureus infection is a common cause of mastitis, reducing milk yield, affecting animal welfare and causing huge economic losses within the dairy industry. In addition to the problem of acquired drug resistance, bacterial invasion into udder cells and the formation of surface biofilms are believed to reduce antibiotic efficacy, leading to treatment failure. Here, we investigated the antimicrobial activities of enrofloxacin, an antibiotic that is commonly used in mastitis therapy and polyhexamethylene biguanide (PHMB), an antimicrobial polymer. The antimicrobial activities were tested against intracellular S. aureus in infected Mac-T cells (host cells). Also, fluorescein-tagged PHMB (PHMB-FITC) was used to study PHMB uptake and localization with S. aureus within the infected Mac-T cells. Anti-biofilm activities were tested by treating S. aureus biofilms and measuring effects on biofilm mass in-vitro. Enrofloxacin and PHMB at 15 mg/L killed between 42 to 92% and 99.9% of intracellular S. aureus respectively. PHMB-FITC entered and colocalized with the intracellular S. aureus, suggesting direct interaction of the drug with the bacteria inside the host cells. Enrofloxacin and PHMB at 15 mg/L reduced between 10% to 27% and 28% to 37% of biofilms’ mass respectively. The half-maximal inhibitory concentrations (IC50) obtained from a cytotoxicity assay were 345 ± 91 and 21 ± 2 mg/L for enrofloxacin and PHMB, respectively; therefore, both compounds were tolerated by the host cells at high concentrations. These findings suggest that both antimicrobials are effective against intracellular S. aureus and can disrupt biofilm structures, with PHMB being more potent against intracellular S. aureus, highlighting the potential application of PHMB in mastitis therapy.